Nursing management of a case of primary hyperhidrosis treated by the three-step auricular acupoint therapy (耳穴“三序”疗法治疗1例原发性多汗症患者的护理体会) - YUAN Dan (袁丹); XIE Wei (谢薇); LIU Qing (刘青); TAN Sha (谭莎); DONG Huaqian (董画千); LIU Xiameng (刘夏梦); ZHAO Lingling (赵玲玲); LUO Liyuan (罗丽媛) (中西医结合护理)
This paper summarized the nursing experience of a patient with primary hyperhidrosis treated by the three-step auricular acupoint therapy. The three-step auricular acupoint therapy refers to a combination of auricular massage, auricular scraping therapy, and auricular acupoint sticking and pressing therapy which applied in a particular sequence. Based on the acupoint selection and nursing by syndrome differentiation, the three-step auricular acupoint therapy is effective to relieve the uncomfortable symptoms in patients with primary hyperhidrosis. (本文总结耳穴“三序”疗法治疗1例原发性多汗症(PH)患者的护理经验, 耳穴“三序”疗法包括耳部按摩、耳部刮痧和耳穴贴压。通过辨证取穴, 实施针对性干预, 能有效缓解PH患者不适症状。)